WARNA SUNGGINGAN DAN KOMPOSISI WAYANG BEBER PACITAN - Salim Salim (Canthing, 2012)
The study entitled "COLOR AND COMPOSITION SUNGGINGAN PACITAN puppet Beber" sunggingan focus on color and composition. The purpose of this study to study, understand and know the colors or patterns sunggingan beber Pacitan puppet with a classification of character and their various attributes are used, as well as sunggingan color and composition. The results of this study are expected to contribute data and add to their repertoire of knowledge, particularly in the field of fine artsResearch using qualitative research methods, to understand color and composition beber Pacitan puppet. The approach used is to describe the aesthetics Fechner works beber Pacitan puppet. Data obtained through observation, interviews, library research, and documentation. Analysis using the analytical interpretation. Geerts theory of symbols used in the book "The Interprestation Culture", in a structured assessment phase involves sunggingan color and composition, the conclusion stage.Finally, it is understood that the findings in this study, namely the existence of actual puppet beber Pacitan can be further developed. Viewed from the standpoint of art, puppet beber Pacitan not be separated from the principles of art including the composition, color and balance. composition is not alarming. Visual elements such as line, color, texture, space and form organized into a unified harmony between the parts with the whole.Similarly, elements that help harmonize the tension, chaos, applied in Pacitan beber pasunggingan puppet. These elements are: contrast, rhythm, climax, balance, and proportion.